Optimal proprioceptive training combined with rehabilitation regimen for lower limb dysfunction in stroke patients: a systematic review and network meta-analysis - Zheng, Kaiqi; Li, Li; Zhou, Yahui; Gong, Xiaokun; Zheng, Gangbin; Guo, Liang (Frontiers in Neurology, 2024)
BackgroundThis study aims to evaluate the optimal rehabilitation regimen for lower limb dysfunction in stroke patients by analyzing the effects of proprioceptive training (PT) in combination with different rehabilitation interventions.MethodsRandomized controlled trials (RCTs) published up to April 23, 2024, were searched from PubMed, Embase, Cochrane Library, Web of Science, CNKI, Wanfang, VIP, and SinoMed. The quality of the included studies was assessed using the Cochrane Risk of Bias tool (ROB 2.0). Network meta-analysis was performed via R studio and STATA 15.0.ResultsA total of 64 RCTs involving 4,084 stroke patients with lower limb dysfunction were included. For balance ability in stroke patients, PT in combination with motor relearning programme (PT + MRP) demonstrated the optimal rehabilitation effect [surface under the cumulative ranking curve (SUCRA) 77.94%]. For lower limb motor function, PT in combination with closed kinematic chain exercises (PT + CKCE) was most effective (SUCRA 88.39%). For walking ability, PT in combination with visual feedback training (PT + VFT) was superior (SUCRA 96.61%). Cluster analysis indicated that PT + CKCE and PT + RT1 were the optimal rehabilitation regimens for lower limb dysfunction in stroke patients.ConclusionPT+MRP was the optimal rehabilitation regimen for improving balance ability in stroke patients; PT+CKCE was the best for enhancing lower limb motor function; and PT+VFT was most effective for improving walking ability. Overall, PT+CKCE and PT+RT1 represented the optimal rehabilitation regimens for lower limb dysfunction in stroke patients, while PT+RT1 is most effective within 5 days of stroke onset.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/#recordDetailsCRD42024548889, PROSPERO CRD42024548889.